The Use and Perceived Barriers of the Partograph at Public Health Institutions in East Gojjam Zone, Northwest Ethiopia - Desalegne Zelellw; Teketo Tegegne (Ubiquity Press, 2018)
Introduction: The partograph is a vital tool used to reduce maternal and fetal mortality and morbidity and to prevent prolonged and obstructed labor, as well as postpartum hemorrhage and fistula formation. This study explored the use and barriers of the partograph among obstetric caregivers in East Gojam Zone, Northwest Ethiopia. Methods and materials: A cross-sectional study design consisting of both quantitative and qualitative methods was utilized. Data was collected through a structured clinical observation checklist and semistructured questions. The content of the checklists was developed according to modified WHO partograph. Thematic analysis was employed using open code software version 3.6. Coding was done immediately after the data was collected. The coded data was defined and categorized into groups. Once the categories were identified and the names given, the data was related to the objectives of the study. Data was crosschecked to ensure consistency between the themes and the categories. Then we summarized the themes and drew conclusions that gave answers to the research questions. Results and conclusion: This study showed that participants believed partograph is an essential tool used to reduce maternal and fetal mortality and morbidity and to prevent prolonged and obstructed labor, as well as postpartum hemorrhage. They explained that work overload, lack of skill and competency, negligence, lack of motivation and a shortage of infrastructure and resources hindered utilization of the partograph.